COMPLEMENTARY AND ALTERNATIVE TREATMENT OF ATOPIC DERMATITIS - D.Sh. Macharadze ("Paediatrician" Publishers LLC, 2010)
The article presents the description of main types of complementary and alternative medicine (CAM) which are used in treatment of atopic dermatitis (AD) in children and adults. Despite widespread use of CAM, its proper mechanisms are unknown. In Russia the most popular methods of CAM are climatotherapy and homeopathy, while dermatological medicines for external use remain main treatment of AD.Key words: children, atopic dermatitis, complementary and alternative medicine.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):70-72)